Caderno orientativo de primeiros socorros - Parente, Ednei Pereira (Brasil, 2023)
The proposal of the first aid guidebook as a didactic and pedagogical resourece that helps teachers and other education professionals in the promotion, prevention and care of possible harm to students’ health, as well as a reference for teaching and learning, thus contributing to the full human formation is na education product related to the research Interface between education and health. In this way, to contribute to the promotion and prevention of health in the context of professional and technologica education, it is worth noting that it does not replace the need for training of teachers and other education professionals at IFAM Campus Coary, in first aid, with, in compliance with Law 13.722/2018 (Lucas Law). The product presents basic knowledge of first aid with themes suggested by the teachers participating in the research, during the workshop, themes for the development of the educational product. It is expected that as didactic pedagogical material it will contribute to the pedagogical work of teachers, reflecting on the importance of knowledge of first aid, fron the perspective of integral human formation.